(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This paper aims to apply cleaner production technology in the Kufa Cement Factory with the aim of reducing the amount of waste resulting from the production process in the factory and increasing production e ciency in the factory with the same amount of inputs used in 2023. This in turn helps reduce production costs per ton of cement produced, and thus work is done according to a strategy of cost leadership and the factory’s ability to control the selling price and thus achieve the factory’s competitive advantage. To achieve this, the researcher relied on the inductive approach in writing the theoretical framework for the research, relying on foreign and Arab books, dissertations, university dissertations, research, and foreign and Arab periodicals related to the subject of the research, and relying on the descriptive analytical approach. Applied research based on a set of methods such as financial statements, personal interviews, and field visits to the Kufa Cement Factory.A set of conclusions were reached, the most important of which are as follows: The application of cleaner production in the factory led to the return of a large portion of the raw materials that were turning into waste with an environmental impact, which the factory bears and bears additional costs for removing them into the production processes and converting them into a final product. Therefore, cleaner production helped reduce the amount of waste and increase production. Applying cleaner production also helps the economic unit reduce the cost of the product and work according to a cost leadership strategy, thus making it possible to control the price and achieve competitive advantage.